2009
DOI: 10.1063/1.3173197
|View full text |Cite
|
Sign up to set email alerts
|

Electrowetting propulsion of water-floating objects

Abstract: This letter describes a propulsion principle along with experimental verification of this principle by which an air-to-water interface vertically oscillated by ac electrowetting generates a quasisteady, “streaming” flow that can be utilized to propel water-floating objects. This propulsion does not require any mechanical moving parts. Using a centimeter-sized boat whose outer surfaces were covered with microfabricated electrowetting electrodes, linear, and rotational motions of the boat were achieved up to max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…The method for this novel propulsion and rotation mechanism is simple yet efficient; this method can possibly be used to propel and maneuver mini/micro-water-floating boats and robots that can be used for water/air quality monitoring systems or security surveillance systems for specific purposes in other industry areas. 83,88 Mita et al 89 developed a silicon-based swimming robot or pond skating device that floats on liquid surfaces through the use of surface tension and is propelled by EWOD. Figure 21 shows the schematics of the propulsion mechanism involved.…”
Section: Propulsion Of Objects Floating On Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The method for this novel propulsion and rotation mechanism is simple yet efficient; this method can possibly be used to propel and maneuver mini/micro-water-floating boats and robots that can be used for water/air quality monitoring systems or security surveillance systems for specific purposes in other industry areas. 83,88 Mita et al 89 developed a silicon-based swimming robot or pond skating device that floats on liquid surfaces through the use of surface tension and is propelled by EWOD. Figure 21 shows the schematics of the propulsion mechanism involved.…”
Section: Propulsion Of Objects Floating On Watermentioning
confidence: 99%
“…Chung et al 83 developed mini/micro-boats or robots, which have no mechanical moving parts and can swim on a water-free surface like a water strider. 84-87 A centimeter-sized mini-boat was fabricated from a thin plastic foil with outer surfaces that were covered with electrodes for EWOD actuation.…”
Section: Propulsion Of Objects Floating On Watermentioning
confidence: 99%
“…Lee et al 8 studied the locomotion of water snails induced by traveling waves at low Reynolds numbers. Chung et al 6 were inspired by beetle larvae's locomotion and developed a centimeter-sized boat attached with electrodes based on electrowetting-on-dielectrics (EWOD) principles to control surface tensions and demonstrated boat maneuvers on a water surface. Mita et al 3 experimentally demonstrated the propulsion of small water-floating objects using microbubbles created by electrolysis and transported by EWOD actuation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, alternative approaches have been developed that are mainly based on capillary forces and electrokinetic methods. 3,6 The previous researches on micro-propulsion mechanisms mostly focused on underwater objects, and studies on the propulsion of water-floating objects are few. Hu et al 7 studied the motion mechanisms of small water-walking insects such as water spiders, while other research groups 3,4,6 demonstrated the propulsion of artificially constructed water striders.…”
Section: Introductionmentioning
confidence: 99%
“…Gradients in surface tension can be produced electrically, chemically, optically, or thermally . In engineered systems, fluid transport using electric fields to cause surface tension gradeints has been widely applied . By using electrically conductive fluids, applied electric potentials will alter the apparent surface tension at a liquid–solid interface.…”
mentioning
confidence: 99%